Physical activity patterns in adults: prevalence and associated factors - Nathalia Cristine Fraga; Nicoly Machado Maciel; Caio Vitor dos Santos Genebra; José Paulo Candido; Thiago Paulo Frascareli Bento; Guilherme Porfírio Cornelio; Rangel dal Bello Biancon; Alberto De Vitta (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2018)
Abstract Background Insufficient practice of physical activity associated with some factors related to life habits increase the risk of non-transmissible chronic diseases and reduce quality of life. Objective Identify the pattern of physical activity and associated factors in adults aged ≥20 years. Method A cross-sectional, population survey conducted with 600 individuals. Data on demographic, socioeconomic and behavioral aspects, work, and physical activities were collected through home interviews. Descriptive, bivariate and Poisson regression analyses were performed. Results Prevalence of insufficient physical activity was 35.0% (95% CI: 31.2-38.9). Zero to four years of schooling [PR=2.35; 95% CI: 1.07-5.15], working in sitting position [PR=1.52; 95% CI: 1.02-2.48], and number of days at the computer [PR=4.60; 95% CI: 2.38-14.28] remained in the final model for females, whereas 0-4 years [PR=2.30; 95% CI: 1.21-4.06] or 5-8 years [PR=3.70; 95% CI: 0.79-4.00] of schooling, working in sitting position [PR=2.22 95% CI: 1.36-3.62], number of days at the computer [PR=2.04; 95% CI: 1.26-3.32], and number of days of TV viewing [PR=2.12; 95% CI: 1.03-4.36] remained in the final model for males. Conclusion High prevalence of insufficient practice of physical activity is associated with schooling, working in sitting position, and number of days at the computer and TV viewing.